2012
DOI: 10.1177/1420326x12469736
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Responses to Changes in Spectral Power Distributions of LED Light

Abstract: Lighting is an indispensable element in buildings, which influences visual comfort, health, well-being, work performance and building energy consumption. Light emitting diode (LED) technologies for illumination have made rapid advancements. Commercially available LED lightings have high luminous efficacies ranging from 60 to 75 lumen per watt and their spectral power distributions (SPD) are easily controllable. This study aims to reveal the potential effects of spectral power distributions of LED lighting on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Background luminance is an important criterion in lighting design and evaluation. However, according to the previous studies, 7,[10][11][12][13]20 only illuminance values were measured and background luminance values were not given in their subjective response tests evaluating brightness perception. Similar workplane illuminance levels and background luminance levels were assumed in the present research and the same luminaires in the same interior finished environment were used.…”
Section: Subjective Evaluations Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…Background luminance is an important criterion in lighting design and evaluation. However, according to the previous studies, 7,[10][11][12][13]20 only illuminance values were measured and background luminance values were not given in their subjective response tests evaluating brightness perception. Similar workplane illuminance levels and background luminance levels were assumed in the present research and the same luminaires in the same interior finished environment were used.…”
Section: Subjective Evaluations Outlinementioning
confidence: 99%
“…Recently, Yun et al. 19,20 reported that subjects tend to perceive more brightness under red colour emphasizing spectral power distribution, as compared to their perception under blue colour. In addition, the potential effects of spectral power distributions of LED lighting on subjective responses including the evaluation on likeness, comfort, preference, clarity, brightness, glare, skin colour, lighting colour, overall satisfaction and work performance were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the subject participating in the experiment. A detailed experimental procedure was given in a study by Yun et al [8].…”
Section: Methodsmentioning
confidence: 99%